The XFM beamline at the Australian Synchrotron. (19th August 2020) - Howard, Daryl L.; de Jonge, Martin D.; Afshar, Nader; Ryan, Chris G.; Kirkham, Robin; Reinhardt, Juliane; Kewish, Cameron M.; McKinlay, Jonathan; Walsh, Adam; Divitcos, Jim; Basten, Noel; Adamson, Luke; et al.
Abstract : The X‐ray fluorescence microscopy (XFM) beamline at the Australian Synchrotron specializes in the spatially resolved detection and speciation determination of elements at the micrometre length scale. The status of its various operational modes and future upgrades are presented. Abstract : The X‐ray fluorescence microscopy (XFM) beamline is an in‐vacuum undulator‐based X‐ray fluorescence (XRF) microprobe beamline at the 3 GeV Australian Synchrotron. The beamline delivers hard X‐rays in the 4–27 keV energy range, permitting K emission to Cd and L and M emission for all other heavier elements. With a practical low‐energy detection cut‐off of approximately 1.5 keV, low‐ Z detection is constrained to Si, with Al detectable under favourable circumstances. The beamline has two scanning stations: a Kirkpatrick–Baez mirror microprobe, which produces a focal spot of 2 µm × 2 µm FWHM, and a large‐area scanning `milliprobe', which has the beam size defined by slits. Energy‐dispersive detector systems include the Maia 384, Vortex‐EM and Vortex‐ME3 for XRF measurement, and the EIGER2 X 1 Mpixel array detector for scanning X‐ray diffraction microscopy measurements. The beamline uses event‐mode data acquisition that eliminates detector system time overheads, and motion control overheads are significantly reduced through the application of an efficient raster scanning algorithm. The minimal overheads, in conjunction with short dwell times per pixel, have allowed XFM to establish techniques such as full spectroscopic XANES fluorescence imaging, XRF tomography, fly scanning ptychography and high‐definition XRF imaging over large areas. XFM provides diverse analysis capabilities in the fields of medicine, biology, geology, materials science and cultural heritage. This paper discusses the beamline status, scientific showcases and future upgrades.